PADDY CULTIVATION AMONG OWNER AND TENANCY FARMERS IN TIRUNELVELI DISTRICT, TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
Paddy is the most important crop and it occupies the largest area in the Indian Union. India is the second largest producer in the world, next only to China. The productivity of paddy in India is low when compared to other countries. At present the development of agriculture does not merely depend upon increasing the agricultural produce and productivity, but also upon the promotion of a better and well organized marketing by which the agricultural goods are moved from the field of the farmer to the places of ultimate consumers.The study is confined to production of paddy in Palayamkottai block, Tirunelveli district of Tamil Nadu. The study concluded that the levels of input application were greater for the owner farmer when compared with the tenancy farmers producing paddy. The more intensive use of energy inputs were done by the owner farmers than by the tenancy farmers. The net income earned would be comparatively higher even though the owner farmers and spent more on cultivation of paddy crops. The total cost for the tenancy farmers was found to be less than that of the owner farmers.